A new LMS based adaptive interference canceller for ECG power line removal - Bharath, H. N.; Prabhu, K. M. M. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/